UPAYA PENINGKATAN KEMAMPUAN KOGNITIF BERHITUNG ANAK DENGAN PERMAINAN BALOK - RAHMAN, RAHMAN (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2024)
The aim of this research is to improve the development of children's cognitive numeracy skills with number block games in the PAUD group for the 2021/2022 school year. This research uses descriptive methods and a qualitative approach in the form of Classroom Action Research (PTK). Place of research in PAUD with address. Data collection using techniques: observation and documentation. The tools used are observation and documentation sheets. Research results (1) Efforts to improve children's ability to count through number block games in PAUD have provided satisfactory results. This is evident from the recapitulation of the assessment of children's ability to count using the number block method. (2) based on research, observations and implementation of improvements in numeracy learning that researchers carried out in group A PAUD, it turned out to have a very positive impact on increasing children's ability to start numeracy. It is recommended: (1) It is hoped that the number block playing method should always be used in initial numeracy learning (2) It is hoped that school principals can apply the number block method as part of the educational unit level curriculum in developing numeracy learning (3) Considering the implementation of this research, of course There are still many shortcomings, so it is hoped that other researchers or teachers can continue to obtain more complex and satisfying findings.